UBAP2L arginine methylation by PRMT1 modulates stress granule assembly - Huang, Chuyu (Cell Death Differ, 2019)
Stress granules (SGs) are discrete assemblies of stalled messenger ribonucleoprotein complexes (mRNPs) that form when eukaryotic cells encounter environmental stress. RNA-binding proteins (RBPs) mediate their condensation by recruiting populations of mRNPs. However, the cellular and molecular mechanisms underlying the role of ubiquitin-associated protein 2-like (UBAP2L) in the regulation of SG dynamics remain elusive. Here, we show that UBAP2L is required for both SG assembly and disassembly. UBAP2L overexpression nucleated SGs under stress-null conditions. The UBAP2L Arg–Gly–Gly (RGG) motif was required for SG competence, and mediated the recruitment of SG components, including mRNPs, RBPs, and ribosomal subunits. The domain of unknown function (DUF) of UBAP2L-mediated interaction with ras GTPase-activating protein-binding protein (G3BP)1/2, and its deletion caused the cytoplasmic–nuclear transport of UBAP2L and G3BP1/2, thereby compromising SG formation. The protein arginine methyltransferase PRMT1 asymmetrically dimethylated UBAP2L by targeting the RGG motif. Increased arginine methylation blocked, whereas its decrease enhanced UBAP2L interactions with SG components, ablating and promoting SG assembly, respectively. These results provide new insights into the mechanisms by which UBAP2L regulates SG dynamics and RNA metabolism.